То, что сильнее: [рассказы] / Мария Метлицкая - Метлицкая Мария (За чужими окнами, 2015)
Экземпляры: аб. ЦБ (15.08.2016) / Инвентарный номер: 2525 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 54 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6